2021
DOI: 10.5397/cise.2020.00010
|View full text |Cite
|
Sign up to set email alerts
|

Calcific tendinitis of the shoulder in the Korean population: demographics and its relation with coexisting rotator cuff tear

Abstract: Background: To evaluate the demographics, clinical and radiographic features of calcific tendinitis of the shoulder in the Korean population, specifically focusing on the incidence of coexisting rotator cuff tear.Methods: Between October 2014 and January 2015, we performed a prospective multicenter study with 506 patients from 11 training hospitals in Korea. We collected data of demographics and radiographic analysis based on simple radiographs, clinical assessments based on visual analog scale (VAS) and the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0
5

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 15 publications
1
7
0
5
Order By: Relevance
“…The female gender, especially those aged 30–60 years, is a more susceptible cohort for RCCT compared with the male gender. As found in previous reports, RCCT occurs more frequently in women, accounting for approximately 52%–79% of the total incidence [ 24 26 ]. Our study is consistent with published findings that a 72.57% prevalence rate confirms that women suffer from more pain.…”
Section: Discussionsupporting
confidence: 66%
“…The female gender, especially those aged 30–60 years, is a more susceptible cohort for RCCT compared with the male gender. As found in previous reports, RCCT occurs more frequently in women, accounting for approximately 52%–79% of the total incidence [ 24 26 ]. Our study is consistent with published findings that a 72.57% prevalence rate confirms that women suffer from more pain.…”
Section: Discussionsupporting
confidence: 66%
“…Even though the main cause of shoulder pain was calcific deposits, rotator cuff tear could be a cause of symptomatic shoulder pain. In this study, the authors [4] suggested that a poor prognosis was shown by patients with persistent symptoms, old age, patients with recurring symptoms, and patients with menstrual irregularities further radiographic study to evaluate rotator cuff tear might be needed in some calcific tendinitis patients with older age and recurrent symptoms.…”
mentioning
confidence: 88%
“…In a study by Yoo et al [4] entitled "Calcific tendinitis of the shoulder in the Korean population: demographics and its relation with coexisting rotator cuff tear" the authors investigated the demographic, clinical, and radiological factors of calcific tendinitis of the shoulder joint in a large number of Koreans and calculated the prevalence of rotator cuff tear associated with calcific tendi-nitis. This was a multicenter study involving a large population.…”
mentioning
confidence: 99%
“…CT may be due to incorrect differentiation of mesenchymal stem cells in the presence of high serum glucose levels (13). Radiography, sonography and magnetic resonance imaging (MRI) can be used to view calcium deposits (1,3,14,15). Limited studies have been performed on the cause and treatment of this disease.…”
Section: Introductionmentioning
confidence: 99%